A Comparative Analysis of Endoscopic-Assisted Transoral and Transnasal Approaches to Parapharyngeal Space: A Cadaveric Study - Sun, Xicai; Yan, Bo; Truong, Huy Q.; Borghei-Razavi, Hamid; Snyderman, Carl H.; Fernandez-Miranda, Juan C. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Background Surgical resection of parapharyngeal space (PPS) tumors is very challenging. An endoscopic-assisted surgical approach to this region requires detailed and precise anatomic knowledge. The main purpose of this study is to describe and compare the detailed anatomy of the PPS via transnasal transpterygoid (TP) and endoscopic-assisted transoral (TO) approaches.Materials and Methods Six fresh injected cadaver heads (12 sides) were prepared for dissection of the PPS via TP and TO approaches. Computed tomography (CT) with image-based navigation (Navigation System II; Stryker, Kalamazoo, Michigan, United States) was used to identify bony structures around the PPS.Results TP and TO approaches could both expose the detailed anatomical structures in the PPS. The TP approach can provide a direct route to the upper PPS, but it is limited inferiorly by the hard palate and laterally by the medial and lateral pterygoid muscles. However, the TO approach can provide a direct route to the lower PPS, but it is difficult to expose the area around the Eustachian tube. The styloglossus and stylopharyngeus muscles could be considered as the safe anterior boundary of the parapharyngeal internal carotid artery (ICA) with the TO approach. Dissection between the stylopharyngeus muscle and the superior pharyngeal constrictor muscle provides direct access to the parapharyngeal ICA.Conclusion The TP and TO approaches provide new strategies to manage lesions in the PPS. The important neurovascular structures of the PPS could be identified with these approaches. The endoscopic-assisted TO approach can provide direct access to the parapharyngeal ICA.
Keywords: anatomy; endoscopic surgery; parapharyngeal space; transoral approach; transpterygoid approach